Audit Committee Characteristics and Audit Reporting Readability - Razieh Alikhani (University of Tehran, 2021)
Objective: The main purpose of the present research is to investigate the relationship between audit committeefeatures and audit reporting readability. Methods: The present research is an applied one in terms of purpose and is descriptive-correlation in terms of method. The Statistic population includes listed firms in the Tehran Stock Exchange during 2014 to 2018 with 72 firms as sample. Results: This research, which has used panel data with fixed effects, indicates the analysed results of the firm data using  multivariate regression method that there is not a significant relationship between audit committee size, audit committee independence and audit committee financial Expertise with Audit reporting readability. Conclusion: Despite the lack of a significant relationship between Audit committee size, audit committee independence and audit committee financial expertise with audit reporting readability need attention to the effectiveness of audit committees’ characteristics is very important.